(untitled) (Semiárida, 2020)
In the experimental field of the Facultad de Agronomía de la Universidad Nacional de La Pampa, situated at 36°46’ south latitude, at 64°16’ west longitud and at 210 metres above sea level; a trial was conducted with 3 conventional varieties of "canola" rapeseed: Wester, Midas and Global, and a experimental hybrid obtained by genetic cytoplasmic malesterility. A late square design was used. The sowing date was august 18, 1987. Planting and harvest were made manually. The CS-002 hybrid surpassed Midas and Global (Tuckey p=0,05) and it also registred the highest percentage of oil and the least of erucic acid and glucosinolates.